2012
DOI: 10.3109/09638288.2011.644024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuropsychological and psychosocial outcomes of decompressive hemicraniectomy following malignant middle cerebral artery infarctions

Abstract: • Malignant middle cerebral artery infarction is a life threatening condition.• The neurosurgical procedure, “decompressive hemicraniectomy” has been shown to be life-saving among patients with this condition.• There is little known about the long-term neuropsychological and psychosocial outcomes following decompressive hemicraniectomy for malignant middle cerebral artery infarction.• This study concludes that neuropsychological impairments are highly probable post-surgery. However, preserved abilities and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Of 615 studies screened and 72 full articles assessed for eligibility, 18 fulfilled our inclusion and quality criteria (Fig. ) . Based on a high risk of selection bias, one study was additionally excluded (the complete validity assessment can be found in the http://onlinelibrary.wiley.com/doi/10.1111/ijs.12329/suppinfo) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 615 studies screened and 72 full articles assessed for eligibility, 18 fulfilled our inclusion and quality criteria (Fig. ) . Based on a high risk of selection bias, one study was additionally excluded (the complete validity assessment can be found in the http://onlinelibrary.wiley.com/doi/10.1111/ijs.12329/suppinfo) .…”
Section: Resultsmentioning
confidence: 99%
“…In the 17 included studies, follow‐up varied from six to 51 months . Of 459 patients who underwent surgical decompression, 134 died during follow‐up, resulting in a pooled mortality of 29·9% (95% CI 25·8–34·4; I 2 = 0·0%) . Thirty‐four patients (10·5%) were lost to follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of such deficits and deficiencies and their high likelihood in patients with an MMI has been described in a case series by McKenna et al [21] . The high risk for severe cognitive impairment and depression was evident in a neuropsychological investigation by Schmidt et al [14] , supporting our finding of a clinically relevant depression in more than half of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…50-75%, and these RCTs substantially changed neurosurgical practice. To date, an ever increasing number of publications have documented the role of DC in malignant MCA infarct patients, addressing not only the potential clinical benefits but also complications and important ethical and quality of life concerns [3]. However, there are some remaining clinical questions regarding malignant MCA infarcts that have been insufficiently addressed in the literature.…”
mentioning
confidence: 99%